Nitrogen acquisition, net production and allometry of Alnus fruticosa at a young moraine in Koryto Glacier Valley, Kamchatka, Russian Far East - Takahashi, Koichi; Homma, Kosuke; Dorezal, Jiri; Yamagata, Kotaro; Vetrova, Valentina P; Hara, Toshihiko (Journal of plant research, 2018)
Alders (Alnus spp.) often dominate at nutrient-poor sites by symbiotic relations with atmospheric nitrogen-fixing bacteria. However, little is known about quantitative relationships between root nodule as a nitrogen acquisition organ and leaf as a carbon acquisition organ. To examine carbon allocation, nitrogen acquisition and net production in nutrient-poor conditions, we examined allocation patterns among organs of shrub Alnus fruticosa at a young 80-year-old moraine in Kamchatka. Slopes of double-log allometric equations were significantly smaller than 1.0 for the root mass, leaf mass and root nodule mass against stem mass, and for the root nodule mass against root mass, indicating that smaller individuals invested disproportionally more biomass into resource-acquiring leaf and root tissues than to supportive tissues compared to older individuals. The slope of allometric equation of root depth against stem height was 0.542, indicating that smaller/younger individuals allocate disproportionally more biomass into root length growth than stem height growth. On the contrary, the root nodule mass isometrically scaled to leaf mass. The whole-plant nitrogen content also isometrically scaled to root nodule mass, indicating that a certain ratio of nitrogen acquisition depended on root nodules, irrespective of plant size. Although the net production per plant increased with the increase in stem mass, the slope of the double-log regression was smaller than 1.0. On the contrary, the net production per plant isometrically increased with leaf mass, root nodule mass and leaf nitrogen content per plant. Since the leaf mass isometrically scaled to root nodule mass, growth of each individual occurred at the leaves and root nodules in a coordinated manner. It is suggested that their isometric increase contributes to the increase in net production per plant for A. fruticosa in nutrient-poor conditions.
Keywords: Root Nodules, Plant; Ice Cover; Nitrogen; kořenové hlízky rostlin; Biomass; Deglaciation; Allometry; Plant Stems; Symbiosis; Alnus; Isometry; olše; Plant Roots; Primary succession; Russia; ledový příkrov; Growth; Root nodule; symbióza; Carbon; biomasa; uhlík; kořeny rostlin; stonky rostlin; dusík; Rusko